Prevalence of Executive Dysfunction in Type 2 Diabetes Mellitus Patients in Mataram - Harahap, Herpan Syafii; Indrayana, Yanna; Hunaifi, Ilsa; Habib, Phillip; Asriningrum, Asriningrum (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
Executive dysfunction is a consequence of type 2 diabetes mellitus decreasing the quality of life of the patients. Currently, its prevalence is still scarce. Early detection of this executive dysfunction is beneficial in improving the clinical outcomes of the patients. This study aims to investigate the prevalence of executive dysfunction among type 2 diabetes mellitus patients in Mataram. This case-control study involving 106 subjects divided into two groups, type 2 diabetes subjects (n=53) and healthy subjects (n=53) in outpatient setting. The data collected from both groups were age, gender, years of education, TMT-B score, and executive function status. The data collected only from type 2 diabetes mellitus group were age, gender, years of education, duration of diabetes, treatments, smoking, hypertension, coronary heart disease, body mass index, and dyslipidemia. There was significant difference in the frequency of executive dysfunction between type 2 diabetes mellitus and healthy subject groups (p0.05). The prevalence of type 2 diabetes mellitus-associated executive dysfunction was 49.1%. Gender was the only characteristics associated with the prevalence of type 2 diabetes mellitus-associated executive dysfunction (OR=0.25; 95%CI=0.07-0.88, p0.05). There was a high prevalence of type 2 diabetes mellitus-associated cognitive impairment and it was associated with female gender.